2018
DOI: 10.1039/c8ra08539k
|View full text |Cite
|
Sign up to set email alerts
|

Linking lignin source with structural and electrochemical properties of lignin-derived carbon materials

Abstract: This study demonstrates the effect of lignin source on the structural and electrochemical properties of lignin-derived carbon materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…Figure 3b shows the high-resolution C1s spectra of HA and PHA. The binding energy peaks centered at 283.04, 283.82, 286.00, and 287.50 eV for HA and at 283.01, 283.76, 286.00, and 287.48 eV for PHA are assignable to C-C, C-H, C-O, and C=O, respectively (see Supplementary Table S3 online) [27][28][29][30] . Compared with HA, the relative amount of C-C in PHA decreased by 18.5%, while C-H increased by 29.6%, which indicated that the relative proportion of protonated C was higher than that of HA.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3b shows the high-resolution C1s spectra of HA and PHA. The binding energy peaks centered at 283.04, 283.82, 286.00, and 287.50 eV for HA and at 283.01, 283.76, 286.00, and 287.48 eV for PHA are assignable to C-C, C-H, C-O, and C=O, respectively (see Supplementary Table S3 online) [27][28][29][30] . Compared with HA, the relative amount of C-C in PHA decreased by 18.5%, while C-H increased by 29.6%, which indicated that the relative proportion of protonated C was higher than that of HA.…”
Section: Resultsmentioning
confidence: 99%
“…The lignin was from the straw plant. The parameters obtained for the purchased lignin are given in Table 1 , and the typical structural units of lignin are described in Figure S1 [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The lignin was from the straw plant. The parameters obtained for the purchased lignin are given in Table 1, and the typical structural units of lignin are described in Figure S1 [23]. ECH (99.5%), NaOH (99.5%), and dimethyl sulfoxide (DMSO, 99.5%) were supplied by Aladdin Biochemical Technology Co., Ltd (Shanghai, China).…”
Section: Materials and Chemicalsmentioning
confidence: 99%
“…For example, in comparing porous carbons generated from a purified Kraft lignin, ethanol‐extracted lignin, and diluted alkali lignin with different molecular weights (MWs), it was found that the lignin MW affected the carbon porosity and electrochemical performance . Following these studies, alkaline‐extracted lignin from hybrid poplar and lodge pole with significant differences in structure and MW were converted to activated carbon materials with distinctive distributions of macro, meso‐ and micro‐pores . Given the well recognized plasticity of lignin biosynthesis and the ability to isolate lignin with little structural change or significant engineered alterations, it is anticipated that we will be able to engineer valuable lignin feedstocks for these electrochemical devices after better defining the fundamental conversion mechanisms in carbonization and activation …”
Section: Applications Of Lignin‐derived Materials In Electrochemical mentioning
confidence: 99%